Identificacion mediante PCR del sexo de la papaya (carica papaya L.), hibrido "Pococi" - Saalau Rojas, E.=700 1 Barrantes Santamaria, W.; Loria Quiros, C.L.; Brenes Angulo, A.; Gomez Alpizar, L.
(Es, En)
Ilus., 26 ref.
Keywords: CARICA PAPAYA; IDENTIFICACION; HERMAFRODITISMO; MARCADORES GENETICOS; PCR; ADN; COSTA RICA; GENES LIGADOS AL SEXO; AGRONOMIA MESOAMERICANA